Alumina ceramic substrate and preparation method thereof
By adding magnesium oxide, complex rare earth oxides, magnesium fluoride and chromate mackerel to the alumina ceramic substrate as a sintering assistant, and using segmented sintering procedures, the aluminum alumina ceramic substrate is in high strength, high temperature, resistance to resistance The problem of insufficient strength and hardness under extreme conditions such as corrosion realizes higher bending strength and hardness.
Patent Information
- Application Number
- CN202411383268.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In the application of existing alumina ceramic substrates under extreme conditions such as high strength, high temperature, corrosion resistance, etc., there are still problems of insufficient strength and hardness, which is difficult to meet more demanding application needs.
By adding magnesium oxide, complex rare earth oxides, magnesium fluoride, and chromate sintering additives to the raw materials of alumina ceramic substrates, combined with segmented sintering procedures to improve the density and mechanical properties of ceramic substrates.
A significant improvement of the bending strength and hardness of the aluminum oxide ceramic substrate, the relative density of more than 99.8%, the volume density ≥3.98g/cm3, the bending strength> 700MPa, the hardness> 18.8GPa, suitable for high strength, high temperature, corrosion resistance, etc. Apply under extreme conditions.
Smart Images

Figure CN118894717B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials and relates to an alumina ceramic substrate and a preparation method thereof. Background Art
[0002] Alumina ceramics are widely used in electronics, machinery, chemicals, medicine, optoelectronics, aerospace and other industries. It can not only be made into integrated circuit substrates, cutting tools, acid and alkali resistant parts, grinding materials, advanced refractory materials and phosphor carriers, but also because of its good biocompatibility, it has also received extensive attention in artificial joints, artificial bones and other devices implanted in the human body. For devices implanted in the human body, the alumina ceramic substrate is required to have not only high mechanical strength, but also high purity. Its purity should reach more than 99% or even higher. At the same time, it must have the characteristics of wear resistance, corrosion resistance, high temperature resistance, good thermal conductivity, high insulation, low dielectric loss, and stable electrical properties. Therefore, how to further improve the purity, strength, hardness and other properties of alumina ceramic substrates used for implanted human body packaging devices has become the current research focus of the alumina ceramic substrate industry.
[0003] In response to the above problems, researchers have adopted various strengthening and toughening methods, such as self-toughening, particle toughening, phase change toughening, etc. Although these methods can improve the purity, strength and hardness of alumina ceramic substrates, these strengthening and toughening methods have a series of disadvantages, such as the immature self-toughening and particle toughening processes, and limited toughening effects; the toughening effect of phase change toughening will drop sharply with the increase of temperature, seriously affecting the high-temperature performance of ceramic materials. For example, Chinese patent CN11705640A discloses an alumina ceramic substrate and a preparation method thereof. This technology uses the introduction of magnesium aluminum spinel to strengthen and toughen the alumina ceramic substrate, and improves the strength of the alumina ceramic substrate. Its strength reaches more than 600MPa, but there are still some disadvantages in the application of semiconductor manufacturing equipment, high-power electronic components and power modules. High mechanical strength is very important for ensuring the long-term stable operation, precise control and reduction of material wear of semiconductor manufacturing equipment. Similarly, in high-power electronic applications, ceramic substrates require high mechanical strength to withstand mechanical stress, thermal cycles and environmental vibrations. High strength can prevent crack formation and extend the service life of devices.
[0004] With the development of society, the alumina ceramic substrate has more stringent requirements on its strength and hardness in the above application fields. Based on this, the present invention aims to provide an alumina ceramic substrate with higher bending strength and greater hardness. Summary of the invention
[0005] In view of the above technical problems, the present invention aims to provide an alumina ceramic substrate and a preparation method thereof, wherein the raw material is mainly composed of alumina, and after being matched with sintering aids such as magnesium oxide, magnesium fluoride, compound rare earth oxide and lanthanum chromate, slurry is prepared by mixing with ethanol, a binder, a plasticizer and a dispersant, and the slurry is tape-cast to obtain a final ceramic substrate. The present invention introduces lanthanum chromate, compound rare earth oxide, magnesium oxide and magnesium fluoride as sintering aids, and lanthanum chromate can reduce the sintering temperature of alumina ceramics, promote grain growth and densification during sintering, and reduce pore formation; during the sintering process of the alumina ceramic substrate, the compound rare earth oxide is mainly concentrated at the grain boundary to form a rare earth oxide phase, thereby strengthening the grain boundary. , hindering grain boundary sliding, improving the strength and hardness of the substrate. At the same time, the compound of erbium oxide and ytterbium oxide can inhibit excessive grain growth, keep the grains small and uniform, refine the grain structure, and improve the fracture toughness and hardness of the material; magnesium oxide plays a role in hindering grain growth in alumina ceramics, and reduces excessive grain growth at high temperature by forming a second phase on the grain surface, keeping the grains small and uniform, thereby improving the strength and hardness of the ceramics; magnesium fluoride promotes the densification between particles by lowering the sintering temperature and activating the diffusion mechanism, which helps to eliminate tiny pores in the material and improve the density of the ceramics; the preparation method of the present invention is simple, the process is easy to control, and the prepared alumina ceramic substrate has a volume density of ≥3.98g / cm 3 , relative density ≥99.8%, flexural strength>700MPa, hardness>18.8GPa.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] An alumina ceramic substrate comprises the following components in parts by weight: 90-99.5 parts of aluminum oxide, 0.05-1 part of magnesium oxide, 0.5-1 part of magnesium fluoride, 0.05-1 part of composite rare earth oxide, 0.05-1 part of lanthanum chromate, 50-70 parts of solvent, 3-8 parts of binder, 3-8 parts of plasticizer, and 1-4 parts of dispersant.
[0008] In the raw materials of the present invention, magnesium oxide, compound rare earth oxide, magnesium fluoride and lanthanum chromate are added as sintering aids. During the sintering preparation process of alumina ceramics, the synergistic effect between the sintering aids further improves the density and mechanical properties of the alumina ceramic substrate. The synergistic effect is as follows: first, the sintering temperature of alumina ceramics can be significantly reduced. Magnesium oxide and magnesium fluoride reduce the energy required for sintering by promoting liquid phase sintering and grain boundary wetting effect, while lanthanum chromate and compound rare earth oxides stabilize the sintering process by introducing the formation of additional phases and inhibiting grain growth; second, under the synergistic effect of several additives, the surface energy is reduced, the wetting between particles and the formation of liquid phase are promoted, the material migration is accelerated, the presence of pores is reduced, and the density of the ceramic is improved. Magnesium oxide, magnesium fluoride and compound rare earth oxides help to improve the densification of the sintered body, while lanthanum chromate further inhibits grain growth, makes the crystal structure tighter, and reduces the defects inside the material. At the same time, magnesium oxide, compound rare earth oxide and lanthanum chromate They jointly inhibit the abnormal growth of alumina grains. Magnesium oxide prevents grain boundary migration by forming a second phase. The presence of compound rare earth oxides at the grain boundary improves the strength of the grain boundary. Lanthanum chromate can further enhance the mechanical properties of the material by forming a spinel structure. Magnesium fluoride provides a better microstructural environment for the action of other additives by promoting densification and reducing the sintering temperature. Finally, the combined effect of the four additives enables the alumina ceramic substrate to form a finer, more uniform grain structure and a densified microstructure during the sintering process. The compound rare earth oxides and lanthanum chromate enhance the grain boundary strength and thermal stability, and comprehensively improve the overall performance of the material, making it suitable for use under extreme conditions such as high strength, high temperature, and corrosion resistance.
[0009] As a limitation of the present invention, the composite rare earth oxide is obtained by ball milling a composite of erbium oxide and ytterbium oxide in a ratio of 3:1 by mass, and the ball milling process is as follows: the material is placed in a ball milling jar and ball milled for 3 cycles at a speed of 200-300 r / min, and one cycle is: forward rotation for 20 minutes, reverse rotation for 20 minutes, and rest for 10 minutes.
[0010] The present invention uses the product of ball milling of composite rare earth oxides as one of the sintering aids. After the two rare earth oxides are ball milled, they can be evenly and fully filled in the alumina powder. Erbium oxide and ytterbium oxide can inhibit the abnormal growth of alumina grains during the sintering process, and can refine the grains, and finally improve the density and flexural strength of the ceramic material after sintering. Specifically, the synergistic effect of the two is as follows:
[0011] 1. Erbium oxide and ytterbium oxide can partially dissolve in alumina to form a solid solution, thereby introducing lattice distortion and internal stress. This internal stress and lattice distortion can inhibit the rapid growth of grains, keeping the grains smaller in size, thereby improving the mechanical strength and toughness of the ceramic;
[0012] 2. The addition of erbium oxide and ytterbium oxide will form a local liquid phase (such as a low-melting-point eutectic phase), which helps to fill the pores between particles and promote diffusion and rearrangement between particles, thereby accelerating the densification rate of the sintering process;
[0013] 3. The addition of erbium oxide and ytterbium oxide can promote the densification of alumina by forming a low melting point liquid phase or changing the grain boundary energy of ceramic materials. Especially during high temperature sintering, these rare earth oxides can react with alumina and its impurities (such as silicon, calcium, magnesium and other oxides) to form composite oxides or eutectics with lower melting points, thereby reducing the sintering temperature;
[0014] 4. During the sintering process, the control of grain growth has an important influence on the performance of the final ceramic material. Erbium oxide and ytterbium oxide can cooperate with each other to adjust the growth rate of grains by adsorbing on the surface of alumina particles or reacting with grain boundaries;
[0015] 5. Erbium oxide and ytterbium oxide promote the densification of materials by reducing grain boundary energy and increasing grain boundary mobility. Since rare earth oxides have higher ionic radius and surface energy, they tend to gather at grain boundaries, reduce grain boundary energy, thereby increasing the migration rate of grain boundaries and promoting densification during sintering;
[0016] 6. Erbium oxide and ytterbium oxide can enhance the toughening effect of materials by refining grains and increasing the number of grain boundaries. The refined grain structure can hinder the expansion of cracks through the "grain boundary strengthening" mechanism, thereby improving the bending strength and fracture toughness of ceramic materials.
[0017] The synergistic effect of erbium oxide and ytterbium oxide will make the microstructure of the ceramic material more uniform, the grain size smaller, and the grain boundaries clearer, which will help improve the comprehensive performance of the ceramic material.
[0018] As a second limitation of the present invention, the binder is one or more of polyvinyl alcohol, polyvinyl butyral ester, hydroxypropyl methylcellulose, and ethyl cellulose.
[0019] As a third limitation of the present invention, the plasticizer is one or more of dibutyl phthalate, polyethylene glycol, glycerol, triethylene glycol, and dioctyl phthalate; the dispersant is one or more of acrylate, propylene glycol methyl ether acetate, polyvinyl pyrrolidone, and triethyl phosphate.
[0020] The present invention also provides a method for preparing an alumina ceramic substrate, which is performed in the following steps in sequence:
[0021] S1: weigh alumina, magnesium oxide, magnesium fluoride, composite rare earth oxide, lanthanum chromate, ethanol, binder, plasticizer and dispersant;
[0022] S2: grinding the weighed aluminum oxide, magnesium oxide, magnesium fluoride, and lanthanum chromate, adding them into a ball mill together with the composite rare earth oxide, solvent, binder, plasticizer, and dispersant to obtain a slurry;
[0023] In the present invention, the raw materials are ball-milled, and the particle size after ball milling has an important influence on the subsequent preparation, molding and performance of the alumina ceramic substrate. Specifically: first, the ball milling process can grind the alumina powder into finer particles, usually reaching the submicron or nanometer level. The refined particles have a larger specific surface area, which helps to form a more uniform slurry in the subsequent tape-casting process; during the ball milling process, the impact and friction of the ball milling medium cause the particles to continuously collide, break and redistribute, thereby obtaining an alumina powder with uniform particle size distribution. This uniform particle distribution can improve the stability of the slurry, avoid particle agglomeration or stratification during the tape-casting process, and ensure the uniformity of the final ceramic substrate; secondly, the ball milling process can effectively dissolve the agglomerates on the surface of the alumina particles, so that the particles are more evenly dispersed in the slurry. Uniformly dispersed particles can reduce the viscosity of the slurry, improve its fluidity and molding properties, and help to obtain a ceramic green body with consistent thickness and no defects. Through ball milling, the particle distribution of the slurry is more uniform, the presence of large particles is reduced, and the friction resistance between particles is reduced, thereby improving the fluidity and plasticity of the slurry, making the tape casting process smoother, reducing the generation of defects, and ultimately improving the overall performance of the ceramic substrate;
[0024] S3: placing the obtained slurry into a vacuum degassing machine for degassing;
[0025] S4: pouring the defoamed slurry into a hopper, casting on a tape casting machine to obtain a wet blank, ventilating, heating and drying in the tape casting machine to obtain a green porcelain strip;
[0026] S5: cutting, laminating, and warm isostatic pressing the green ceramic strip to obtain a green alumina ceramic substrate;
[0027] S6: Debinding and sintering the ceramic substrate green body to obtain an alumina ceramic substrate.
[0028] As a limitation of the method for preparing an alumina ceramic substrate of the present invention, in step S2, the ball milling speed is 300 r / min, and the ball milling is performed for three cycles, each cycle is forward rotation for 25 minutes, reverse rotation for 25 minutes, and rest for 10 minutes.
[0029] As a second limitation of the method for preparing an alumina ceramic substrate of the present invention, in step S3, the debubbling time is 20-120 min, and the debubbling pressure is 0.8-1.0 kPa.
[0030] As a third limitation of the method for preparing an alumina ceramic substrate of the present invention, in step S5, the warm isostatic pressing temperature is 80° C., the pressure is 800-2000 psi, and the holding time is 50-70 min.
[0031] As the last limitation of the method for preparing an alumina ceramic substrate of the present invention, in step S6, the sintering is performed in the following order:
[0032] (a) The first heating stage is to heat from room temperature to 400-600°C and keep the temperature for 180-300 min;
[0033] (b) The second heating stage, from 400~600℃ to 950~1050℃, keeping temperature for 60~120min;
[0034] (c) The third heating stage, from 950-1050°C to 1350-1430°C, keeping temperature for 120-180 min;
[0035] (d) Cooling stage: first cool to 800℃ and then cool to room temperature along with the furnace.
[0036] As is known to all, the sintering process is the process of material nucleation and growth. The sintering process of the present invention will affect the grain size, pore size, pore shape, density, etc. of the alumina ceramic substrate, which is closely related to the density and mechanical properties of the alumina ceramic substrate. The present invention adopts a three-stage heating method for sintering. Sintering will make the grain size smaller and more uniform, affecting its strength and hardness; the pore size is infinitely reduced, affecting the density of the substrate; the pore shape tends to be spherical, affecting the mechanical strength of the substrate and reducing stress concentration. Therefore, controlling the sintering conditions is crucial to controlling the grain size, pore size and pore shape of the alumina ceramic substrate.
[0037] In the sintering process of the present invention, the first temperature rising stage is from room temperature to 400-600°C, during which the volatilization process of organic matter occurs. If the holding time in this stage is greater than 300 minutes, microstructural defects, reduced sintering efficiency, increased energy consumption and decreased substrate performance will result; if the holding time is less than 180 minutes, organic matter will remain, internal pores and defects will be formed, sintering densification will be insufficient and mechanical, electrical and thermal properties will be decreased, thereby affecting the overall quality and reliability of the alumina ceramic substrate. The second heating stage is from 400~600℃ to 950~1050℃. This stage further ensures the complete decomposition and removal of organic matter, promotes initial sintering and densification, stabilizes the internal structure and reduces stress concentration. In this stage, the holding time of more than 120min may lead to adverse consequences such as excessive volume shrinkage and internal stress accumulation. The holding time of less than 60min will result in insufficient initial sintering, incomplete decomposition of organic matter and uneven temperature distribution, which will affect the sintering effect. The third heating stage is from 950~1050℃ to 1350~1430℃. This stage promotes sintering. Densification, elimination of internal defects, uniform grain growth, grain rearrangement and grain boundary strengthening, stress release and improved dimensional stability. If the holding time in this stage is more than 180 minutes, the grains will grow abnormally, the mechanical properties will decrease, and the manufacturing cost and energy consumption will increase. If it is less than 120 minutes, it will lead to defects such as insufficient densification, residual internal defects of the material, unstable grain structure, and residual stress not released. In the cooling stage, the temperature should be cooled to 800℃ first, and then cooled with the furnace. The first cooling stage can prevent the accumulation of thermal stress and crack formation, and help stabilize the crystal structure, thereby improving the mechanical properties of the ceramic.
[0038] As a further limitation of the method for preparing an alumina ceramic substrate of the present invention, in step S6, the rate of the sintering stage is performed according to the following procedure:
[0039] The heating rate of the first heating stage is 0.5~2.5℃ / min; the heating rate of the second heating stage is 0.5~2℃ / min; the heating rate of the third stage is 0.5~3℃ / min; and the rate of the cooling stage is 1~3℃ / min.
[0040] When the heating rate in the first stage of the present invention is greater than 2.5°C / min, it will lead to adverse consequences such as incomplete decomposition of organic matter, insufficient removal of internal gas, thermal stress concentration and uneven sintering process. When the heating rate is less than 0.5°C / min, it will lead to the risk of incomplete degreasing or increased thermal stress. When the heating rate in the second stage is greater than 2°C / min, it will lead to insufficient sintering densification, formation of pores and defects, increased thermal stress, phase change and uneven grain growth, which will ultimately affect the mechanical properties, electrical properties and thermal properties of the ceramic substrate. However, when the heating rate is less than 0.5°C / min, it will lead to abnormal growth of sintered grains and the generation of microcracks. When the heating rate in the third heating stage is greater than 3℃ / min, it will lead to a series of adverse consequences such as insufficient sintering densification, the formation of pores and defects, abnormal grain growth, grain boundary weakening, mechanical property degradation and warping deformation. However, when the heating rate is less than 0.5℃ / min, it will lead to abnormal grain growth, excessive sintering leading to reduced density, and increased risk of local melting or deformation. When the rate in the cooling stage is greater than 3℃ / min, it will lead to increased thermal stress inside the ceramic substrate, crack and defect formation, uneven grain structure, material deformation and warping, reduced mechanical properties and insufficient residual stress release. However, when the cooling rate is less than 1℃ / min, it will lead to a longer sintering cycle and increased production costs.
[0041] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.
[0042] The above technical solution has the following advantages or beneficial effects:
[0043] The alumina ceramic substrate prepared by the present invention has excellent performance, a relative density of more than 99.8%, and a volume density of ≥3.98g / cm 3 , flexural strength can reach more than 700MPa, hardness>18.8GPa;
[0044] The preparation method of the present invention is simple, the process is easy to control, the cycle is short, and it is convenient for industrial application;
[0045] The present invention adds magnesium oxide, compound rare earth oxide, magnesium fluoride and lanthanum chromate as sintering aids to the raw materials of the alumina ceramic substrate. The synergistic effect between the sintering aids further improves the density and grain uniformity of the alumina ceramic substrate, thereby obtaining a more uniform grain structure and excellent mechanical properties.
[0046] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1This is a comparison diagram of the alumina ceramic substrate prepared in Example 1 of the present invention before and after sintering;
[0048] Figure 2 This is a SEM image of the fracture of the alumina ceramic substrate prepared in Example 1 of the present invention;
[0049] Figure 3 This is a SEM image of the fracture surface of the alumina ceramic substrate prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0050] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0051] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified. Example 1
[0052] This embodiment prepares an alumina ceramic substrate, and the preparation process and steps are as follows:
[0053] S1: Weigh 99g of high-purity (99.9%, the same below) aluminum oxide nanopowder, 0.2g of magnesium oxide, 0.4g of compound rare earth oxide (erbium oxide and ytterbium oxide are compounded in a mass ratio of 3:1 and ball-milled, and the ball-milling process is as follows: the materials are placed in a ball milling jar and ball-milled at a speed of 200r / min for 3 cycles, and one cycle is: forward rotation for 20min, reverse rotation for 20min, and rest for 10min), 0.8g of magnesium fluoride, 0.1g of lanthanum chromate, 62g of ethanol, 8g of polyvinyl butyral, 8g of dioctyl phthalate, and 3g of triethyl phosphate;
[0054] S2: After sand grinding, weighed aluminum oxide, magnesium oxide, magnesium fluoride, and lanthanum chromate were added into a ball mill together with compound rare earth oxide, ethanol, polyvinyl butyral ester, dioctyl phthalate, and triethyl phosphate for ball milling at a speed of 300 r / min. The ball milling was repeated for three cycles, with each cycle running forward for 25 min, reverse for 25 min, and resting for 10 min to obtain a slurry with a particle size D50 of 0.3 μm and a solid content of 62%;
[0055] S3: The obtained slurry is placed in a vacuum degassing machine for degassing for 30 minutes, and the degassing pressure is 0.8 kPa;
[0056] S4: pouring the ceramic slurry into a hopper, setting the casting thickness to 150 μm, forming a wet blank on a casting machine, ventilating, heating and drying in the casting machine to obtain a green ceramic strip;
[0057] S5: cutting the raw ceramic strip, selecting ten layers of strips for lamination, keeping the temperature at 80° C. and 1000 psi for 60 minutes, and obtaining a green alumina ceramic substrate;
[0058] S6: The obtained alumina ceramic substrate green body is heated from room temperature to 500°C at a heating rate of 2.5°C / min, kept warm for 180 minutes, then heated to 1050°C at a heating rate of 2°C / min, kept warm for 60 minutes, then heated to 1420°C at a heating rate of 3°C / min, kept warm for 180 minutes, and finally cooled to 800°C at a rate of 3°C / min, and then cooled along with the furnace.
[0059] Figure 1 This is a comparison diagram of the alumina ceramic substrate prepared in Example 1 of the present invention before and after sintering. It can be seen from the figure that the surface of the ceramic substrate after sintering is more glossy than that before sintering, and the radial shrinkage rate is about 17.15%.
[0060] Figure 2 This is a SEM image of the fracture of the alumina ceramic substrate prepared in Example 1 of the present invention. It can be seen from the image that the grain size is uniform and dense, and there are no abnormal grains and abnormal bubbles and cavities. Example 2
[0061] This embodiment prepares an alumina ceramic substrate, and the preparation process and steps are as follows:
[0062] S1: Weigh 99.5g of high-purity alumina nanopowder, 0.05g of magnesium oxide, 1g of compound rare earth oxide (erbium oxide and ytterbium oxide are compounded in a mass ratio of 3:1 and obtained by ball milling. The ball milling process is as follows: the materials are placed in a ball milling jar and ball milled at a speed of 250r / min for 3 cycles. One cycle is: forward rotation for 20min, reverse rotation for 20min, and rest for 10min), 0.5g of magnesium fluoride, 1g of lanthanum chromate, 50g of ethanol, 5g of polyvinyl butyral, 6g of dioctyl phthalate, and 4g of triethyl phosphate;
[0063] S2: After sand grinding, weighed aluminum oxide, magnesium oxide, magnesium fluoride, and lanthanum chromate were added into a ball mill together with compound rare earth oxide, ethanol, polyvinyl butyral ester, dioctyl phthalate, and triethyl phosphate for ball milling at a speed of 300 r / min. The ball milling was repeated for three cycles, with each cycle running forward for 25 min, reverse for 25 min, and resting for 10 min to obtain a slurry with a particle size D50 of 0.3 μm and a solid content of 62%;
[0064] S3: The obtained slurry is placed in a vacuum degassing machine for degassing for 20 minutes, and the degassing pressure is 0.9 kPa;
[0065] S4: pouring the ceramic slurry into a hopper, setting the casting thickness to 200 μm, forming a wet blank on a casting machine, ventilating, heating and drying in the casting machine to obtain a green ceramic strip;
[0066] S5: cutting the raw ceramic strip, selecting ten layers of strips for lamination, keeping the temperature at 80° C. and 2000 psi for 70 minutes, and obtaining a green alumina ceramic substrate;
[0067] S6: The obtained alumina ceramic substrate green body is heated from room temperature to 600°C at a heating rate of 2°C / min, kept at this temperature for 250min, then heated to 1000°C at a heating rate of 1.5°C / min, kept at this temperature for 120min, then heated to 1430°C at a heating rate of 0.5°C / min, kept at this temperature for 150min, and finally cooled to 800°C at a rate of 2°C / min, and then cooled with the furnace. The debinding process is completed synchronously in the first heating stage.
[0068] Figure 3 This is a SEM image of the fracture of the alumina ceramic substrate prepared in Example 2 of the present invention. It can be seen from the image that the grain size is uniform and dense, and there are no abnormal grains and abnormal bubbles and cavities. Example 3
[0069] This embodiment prepares an alumina ceramic substrate, and the preparation process and steps are as follows:
[0070] S1: Weigh 90g of high-purity alumina nanopowder, 1g of magnesium oxide, 0.05g of compound rare earth oxide (erbium oxide and ytterbium oxide are compounded in a mass ratio of 3:1 and ball-milled. The ball-milling process is as follows: the materials are placed in a ball mill and ball-milled at a speed of 300r / min for 3 cycles. One cycle is: forward rotation for 20min, reverse rotation for 20min, and rest for 10min), 1g of magnesium fluoride, 0.05g of lanthanum chromate, 70g of ethanol, 3g of polyvinyl alcohol, 3g of dibutyl phthalate, and 1g of acrylate;
[0071] S2: After sand grinding, weighed aluminum oxide, magnesium oxide, magnesium fluoride, composite rare earth oxide, and lanthanum chromate are added into a ball mill together with composite rare earth oxide, ethanol, polyvinyl alcohol, dibutyl phthalate, and acrylate for ball milling at a speed of 300 r / min. The ball milling is repeated for three cycles, with each cycle running forward for 25 min, reverse for 25 min, and resting for 10 min to obtain a slurry with a particle size D50 of 0.3 μm and a solid content of 62%;
[0072] S3: The obtained slurry is placed in a vacuum degassing machine for degassing for 120 minutes at a degassing pressure of 1.0 kPa;
[0073] S4: pouring the ceramic slurry into a hopper, setting the casting thickness to 200 μm, forming a wet blank on a casting machine, ventilating, heating and drying in the casting machine to obtain a green ceramic strip;
[0074] S5: cutting the raw ceramic strip, selecting ten layers of strips for lamination, keeping the temperature at 80° C. and 800 psi for 50 minutes, and obtaining a green alumina ceramic substrate;
[0075] S6: The obtained alumina ceramic substrate green body is heated from room temperature to 400°C at a heating rate of 0.5°C / min, kept at this temperature for 300min, then heated to 950°C at a heating rate of 0.5°C / min, kept at this temperature for 90min, then heated to 1350°C at a heating rate of 1.5°C / min, kept at this temperature for 120min, finally cooled to 800°C at a rate of 1°C / min, and then cooled with the furnace. The debinding process is completed synchronously in the first heating stage. Comparative Example
[0076] In order to explore the effects of different sintering aids and sintering processes on the performance of the alumina ceramic substrate in the present invention, the following comparative experiments were conducted. Different alumina ceramic substrates were prepared in the following comparative examples, as follows:
[0077] Comparative Example 1
[0078] In this comparative example, an alumina ceramic substrate similar to that of Example 1 is prepared, with the only difference being that in step S1, no composite rare earth oxide is added.
[0079] Comparative Example 2
[0080] In this comparative example, an alumina ceramic substrate similar to that of Example 1 is prepared, except that magnesium fluoride is not added in step S1.
[0081] Comparative Example 3
[0082] In this comparative example, an alumina ceramic substrate similar to that of Example 1 is prepared, except that in step S1, magnesium oxide is not added.
[0083] Comparative Example 4
[0084] In this comparative example, an alumina ceramic substrate similar to that of Example 1 is prepared, except that in step S1, lanthanum chromate is not added.
[0085] Comparative Example 5
[0086] In this comparative example, an alumina ceramic substrate similar to that of Example 1 is prepared, with the only difference being that in step S1, no composite rare earth oxide is added, and only erbium oxide is added.
[0087] Comparative Example 6
[0088] In this comparative example, an alumina ceramic substrate similar to that of Example 1 is prepared, except that in step S1, no composite rare earth oxide is added, and only ytterbium oxide is added.
[0089] Comparative Example 7
[0090] The present comparative example prepares an alumina ceramic substrate similar to that of Example 1, except that in step S6, the temperature is directly raised from room temperature to 1420°C at a heating rate of 3°C / min without performing stage-by-stage heating, and then kept at that temperature for 240 minutes, and then cooled to room temperature in the furnace.
[0091] Performance Testing
[0092] In order to verify the quality of the finished alumina ceramic substrates prepared by the preparation method provided by the present invention, the alumina ceramic substrates prepared by the above Examples 1-3 and Comparative Examples 1-7 were tested, and the test results are shown in the following table.
[0093]
[0094] It can be seen from the above table that the volume density, bending strength and hardness of the alumina ceramic substrates prepared in Examples 1-3 are greatly improved compared with those in Comparative Examples 1-7. It can be seen that the alumina ceramic substrates prepared by the preparation method provided by the present invention have better mechanical properties.
[0095] In summary, the volume density of the alumina ceramic substrate prepared by the preparation method provided by the present invention is ≥3.98 g / cm 3 , flexural strength>700MPa, hardness>18.8GPa.
[0096] The present invention adds magnesium oxide, compound rare earth oxide, magnesium fluoride and lanthanum chromate as sintering aids to the raw materials of the alumina ceramic substrate. Through the synergy between alumina and the aids, the density and grain uniformity of the alumina ceramic substrate are further improved during the sintering process, thereby obtaining a more uniform grain structure and excellent mechanical properties; in addition, the staged heating program adopted in the sintering process of the present invention also has a positive effect on the grain size, pore size and pore shape of the alumina ceramic substrate, thereby obtaining an alumina ceramic substrate with higher bending strength and greater hardness.
[0097] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.
Claims
1. An alumina ceramic substrate, characterized in that: The alumina ceramic substrate comprises the following components in parts by weight: 90-99.5 parts of alumina, 0.05-1 parts of magnesium oxide, 0.5-1 parts of magnesium fluoride, 0.05-1 parts of composite rare earth oxide, 0.05-1 parts of lanthanum chromate, 50-70 parts of ethanol, 3-8 parts of binder, 3-8 parts of plasticizer, and 1-4 parts of dispersant; The composite rare earth oxide is obtained by ball milling a composite of erbium oxide and ytterbium oxide in a mass ratio of 3:
1. The ball milling process is as follows: the material is placed in a ball milling jar and ball milled for 3 cycles at a speed of 200 to 300 r / min. One cycle is: forward rotation for 20 minutes, reverse rotation for 20 minutes, and rest for 10 minutes. The method for preparing the alumina ceramic substrate is carried out in the following steps in sequence: S1: weigh alumina, magnesium oxide, magnesium fluoride, composite rare earth oxide, lanthanum chromate, ethanol, binder, plasticizer and dispersant; S2: grinding the weighed aluminum oxide, magnesium oxide, magnesium fluoride, and lanthanum chromate, adding the mixed rare earth oxide, ethanol, a binder, a plasticizer, and a dispersant into a ball mill for mixing to obtain a slurry; S3: placing the obtained slurry into a vacuum degassing machine for degassing; S4: pouring the defoamed slurry into a hopper, casting on a tape casting machine to obtain a wet blank, ventilating, heating and drying in the tape casting machine to obtain a green porcelain strip; S5: cutting, laminating, and warm isostatic pressing the green ceramic strip to obtain a green alumina ceramic substrate; S6: debinding and sintering the green body of the alumina ceramic substrate to obtain an alumina ceramic substrate; The sintering process is carried out in the following order: (a) In the first heating stage, the temperature is raised from room temperature to 400-600°C at a heating rate of 0.5-2.5°C / min and kept at this temperature for 180-300 min; (b) The second heating stage, heating from 400-600°C to 950-1050°C at a heating rate of 0.5-2°C / min, and keeping the temperature for 60-120 min; (c) The third heating stage, heating from 950-1050°C to 1350-1430°C at a rate of 0.5-3°C / min, and keeping the temperature for 120-180 min; (d) Cooling stage: first cool to 800℃ at a cooling rate of 1~3℃ / min, and then cool to room temperature along with the furnace.
2. The alumina ceramic substrate according to claim 1, characterized in that: The binder is one or more of polyvinyl alcohol, polyvinyl butyral, hydroxypropyl methylcellulose and ethyl cellulose.
3. The alumina ceramic substrate according to claim 1, characterized in that: The plasticizer is one or more of dibutyl phthalate, polyethylene glycol, glycerol, triethylene glycol, and dioctyl phthalate; the dispersant is one or more of acrylate, propylene glycol methyl ether acetate, polyvinyl pyrrolidone, and triethyl phosphate.
4. The method for preparing an alumina ceramic substrate according to claim 1, characterized in that: In step S2, the ball milling speed is 300 r / min, and the ball milling is performed for three cycles, each cycle is 25 minutes of forward rotation, 25 minutes of reverse rotation, and 10 minutes of rest.
5. The method for preparing an alumina ceramic substrate according to claim 1, characterized in that: In step S3, the defoaming time is 20-120 min, and the defoaming pressure is 0.8-1.0 kPa.
6. The method for preparing an alumina ceramic substrate according to claim 1, characterized in that: In step S5, the warm isostatic pressing temperature is 80° C., the pressure is 800-2000 psi, and the holding time is 50-70 min.
Citation Information
Patent Citations
Preparation method of aluminum oxide ceramic for semiconductor equipment
CN116332630A
Alumina ceramic with high thermal shock resistance and preparation method thereof
CN117185785A